2018
DOI: 10.5152/tud.2018.98404
|View full text |Cite
|
Sign up to set email alerts
|

The outcomes of transurethral incision/resection of the prostate (TUIP/TURP) performed early after renal transplantation

Abstract: Objective: In the early period after renal transplantation, urinary retention stemming from bladder outlet obstruction (BOO) may directly affect graft success. The aim of this study was to evaluate the early and long-term outcomes of transurethral resection of the prostate (TURP) and transurethral incision of prostate (TUIP) procedures performed in the first month following RT due to BOO. Material and methods:Between February 2009 and March 2016, 38 male patients underwent TURP/ TUIP due to BOO within the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 25 publications
0
10
0
2
Order By: Relevance
“…Another cause of PVR is BOO, which develops due to benign prostate hyperplasia (BPH). It should be kept in mind that male kidney transplant candidates over 50 are at a higher risk for BOO [23]. However, surgical treatment before transplantation is not recommended in patients undergoing dialysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another cause of PVR is BOO, which develops due to benign prostate hyperplasia (BPH). It should be kept in mind that male kidney transplant candidates over 50 are at a higher risk for BOO [23]. However, surgical treatment before transplantation is not recommended in patients undergoing dialysis.…”
Section: Discussionmentioning
confidence: 99%
“…Because anuria will persist following the transurethral resection of prostate (TURP), these patients will be at high risk for development of bladder neck contracture in the postoperative period [24]. In addition to the initiation of alpha blockers in patients with severe lower urinary tract symptoms, it was shown that TURP or transurethral incision of the prostate (TUIP) operations can be performed safely in the first month after transplantation [23].…”
Section: Discussionmentioning
confidence: 99%
“…It should be known that it is very difficult to predict the incidence of BOO in these patients due to oliguria or anuria resulting from dialysis [36]. Evaluation of the literature concerning the outcomes of TURP in ESRD patients diagnosed with BPH prior to transplantation shows that oliguria or anuria increases the risk of postoperative bladder neck obstruction in these patients [37]. For this reason, in patients who are oliguric or anuric and diagnosed with BPH pretransplantation, it is recommended to perform the operation after transplantation due to the high risk of morbidity [38].…”
Section: Bladder Outlet Obstructionmentioning
confidence: 99%
“…A risk of surgery that should be avoided during this period is damage to the ureterovesical anastomosis created during transplantation. Therefore, it is recommended that a cystography be performed preoperatively and that the operation be initiated after confirming that there is no DOI: 10.1159/000512885 anastomotic leak [37]. In addition, low-pressure irrigation and complete hemostasis to prevent clot retention during surgery will reduce postoperative morbidity.…”
Section: Bladder Outlet Obstructionmentioning
confidence: 99%
See 1 more Smart Citation